Strategi Peningkatan Pendapatan Asli Daerah Kota Surbaya - M. Nur Aulia Rahman; Sri Kamariyah; Zainal Fatah (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2026)
This research aims to analyze the strategies for increasing Local Own-Source Revenue (Pendapatan Asli Daerah/PAD) implemented by the Regional Revenue Agency (Badan Pendapatan Daerah/Bapenda) of Surabaya City. As the second largest city in Indonesia and the capital of East Java Province, Surabaya has significant potential for local revenue that needs to be optimized to support regional development. Using SWOT analysis framework and strategic management theory from David, this study examines the strengths, weaknesses, opportunities, and threats in PAD management, as well as the strategies formulated and implemented to increase revenue. This qualitative research employs a descriptive approach with data collection through in-depth interviews, observation, and documentation study at Bapenda Surabaya City during June-August 2025. Informants include agency leaders, division heads, tax and retribution collectors, and taxpayers. The results indicate that Surabaya City has successfully increased its PAD from Rp 5.2 trillion in 2022 to Rp 6.8 trillion in 2024, representing a 31% growth. Key strategies implemented include digital transformation of tax services through e-tax system, intensification of existing tax sources, extensification through identification of new taxpayers, improvement of taxpayer compliance through education and enforcement, and inter-agency collaboration for data integration. The study identifies several challenges including tax evasion, outdated property valuations, and limited human resources. This research recommends strengthening digital infrastructure, updating tax object databases, enhancing taxpayer awareness programs, improving coordination with central government, and developing performance-based incentive systems for revenue collectors.